Systematic review on the implementation of metrological assurance systems for medical devices in Latin America - Farfán-Vargas, Harold M.; Espinoza-Morriberon, Dante; Moya-Salazar, Marcia M.; Contreras-Pulache, Hans; Moya-Salazar, Jeel (Frontiers in Medicine, 2024)
Background Metrology plays a crucial role in small healthcare service businesses to ensure the quality of products and services. While legal metrology in healthcare exists in some regions, it lacks harmonization. In other countries, there is limited presence of metrology in medical and biomedical engineering. We aimed to evaluate the implementation of metrological assurance systems for medical devices in Latin America. Methods A systematic review was conducted following PRISMA 2020 guidelines and registered with PROSPERO (CRD42022359284). Searches were performed across 13 databases from October 30th to November 3rd, 2022. The search equation was “(((quality assurance) AND (metrology)) AND (medical devices)).” A total of 7,789 documents were identified, of which only 16 met the inclusion criteria. Results The majority of studies (75%) were conducted in Colombia, with a significant portion being undergraduate theses. The primary normative references used in the analyzed studies were ISO 10012 and ISO 17025, with the majority (68.75%) relying on national legislation for their approach. One study in Colombia referenced eight standards, and one in Brazil analyzed user involvement in medical device management. Among the included studies, 56.25% were conducted in healthcare institutions, mainly clinics. Most studies provided implementation guidelines, with ISO 10012 being prominent, alongside ISO 17025, which implicitly addresses ISO 9001 elements. Global bias was low across all studies. Conclusion Our results underscore the importance of metrological assurance in managing medical devices in Latin America. The utilization of international standards and national legislation illustrates the diverse approaches adopted by different institutions. Future research should focus on optimizing metrological practices to enhance quality and safety in healthcare.